2018
DOI: 10.5539/gjhs.v10n4p114
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Breast Diseases Among Women Attending Breast Diseases Diagnosing Center in Erbil City/Iraq

Abstract: Background and Objectives: Breast diseases in women, whether benign or malignant, are very commonly encountered. The pattern of breast diseases varies within countries. The aim of this study was to identify the patterns of breast diseases and their association with different variables in women attending breast diseases diagnosing center in Erbil city/Iraq. Material and Methods:A cross-sectional study conducted at breast diseases diagnosing center in Erbil city from 1 st of April till 1 st of December /2017. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…A total of 50 cases were studied. In the present study, out of 50 cases, 70% of cases were benign and 30% were malignant, correlating with other studies shown in the table number 4 in which studies of Kalyani et al [1] , Arya et al [13] , Rasheed et al [14] , Arunima et al [15] , Zena Habeeb et al [10] , Nazar Hussain et al [16] and Malik R [17] , were comparable with our present study and showed almost equivalent results that benign lesions are more common than malignant lesions. The present study shows left side breast dominance (53.5%) and the findings are similar with the studies of Raju et al [18] , Kalyani et al [1] , Ngwogu et al [7] ; while right side dominance was seen in the studies of Mima.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…A total of 50 cases were studied. In the present study, out of 50 cases, 70% of cases were benign and 30% were malignant, correlating with other studies shown in the table number 4 in which studies of Kalyani et al [1] , Arya et al [13] , Rasheed et al [14] , Arunima et al [15] , Zena Habeeb et al [10] , Nazar Hussain et al [16] and Malik R [17] , were comparable with our present study and showed almost equivalent results that benign lesions are more common than malignant lesions. The present study shows left side breast dominance (53.5%) and the findings are similar with the studies of Raju et al [18] , Kalyani et al [1] , Ngwogu et al [7] ; while right side dominance was seen in the studies of Mima.…”
Section: Methodssupporting
confidence: 91%
“…Due to lack of awareness and education, patients present with advanced disease. The pattern and etiology of breast disease differs in different countries [10,11] . The aim of this study is to find out the various histopathological patterns and distribution of neoplastic breast lesions in various age groups in our institute.…”
Section: Introductionmentioning
confidence: 99%
“…1 case of lipoma underwent excision. 1 case of hypertrophic axillary tail of breast, 1 case of duct ectasia and 2 cases of sebaceous cyst underwent excision, which is comparable with that of Gunes ME et al [17].…”
Section: Discussionsupporting
confidence: 81%